Two for the road - Butcher, Nancy (New York : HarperEntertainment, 2001)
The twins' school trip to Florida starts off smashingly as Ashley is made captain of the triathlon team, but the adventure turns sour when Mary-Kate loses her diary and the dreaded Dana Woletsky shows up and tries to steal the loyalty of Ashley's team and the affection of her boyfriend.
"A Parachute Press book."
5.5
3-6.
3-6
Keywords: Dating (Social customs) -- Fiction; Diaries -- Fiction; Twins -- Fiction; Dating (Social customs) -- Fiction; Diaries -- Fiction; Twins -- Fiction; Florida -- Fiction; Florida -- Fiction